2006
DOI: 10.1111/j.1525-1446.2006.230306.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Community‐Based Outreach Worker Program for Children With Asthma

Abstract: Short-term community-based AOW services for children can be effective in enhancing self-management capabilities, improving the quality of life, increasing the use of asthma management plans, and helping families reduce asthma triggers in the home environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 19 publications
1
34
0
Order By: Relevance
“…[36][37][38][39][40] Of the eight pre-post studies, five showed a significant decrease in ED visits relative to a baseline measurement, [41][42][43][44][45] and one had no significant decrease. 46 Two pre-post studies did not indicate statistical significance; of these, one intervention resulted in a decrease in ED visits 47 and one in an increase in ED visits. 48 There were three cohort studies that examined ED use, two of which showed significant decreases in ED use in the intervention group.…”
Section: Emergency Department Visitsmentioning
confidence: 99%
See 4 more Smart Citations
“…[36][37][38][39][40] Of the eight pre-post studies, five showed a significant decrease in ED visits relative to a baseline measurement, [41][42][43][44][45] and one had no significant decrease. 46 Two pre-post studies did not indicate statistical significance; of these, one intervention resulted in a decrease in ED visits 47 and one in an increase in ED visits. 48 There were three cohort studies that examined ED use, two of which showed significant decreases in ED use in the intervention group.…”
Section: Emergency Department Visitsmentioning
confidence: 99%
“…34,35,37,39,40,51 One showed a significant decrease relative to the control. 36 Of the seven pre-post studies that assessed hospitalization, all showed a decrease in hospitalizations, 41,[43][44][45][46][47][48] but only five indicated statistical significance. 41,[43][44][45][46] Three cohort studies assessed the effect of the intervention on hospitalizations.…”
Section: Emergency Department Visitsmentioning
confidence: 99%
See 3 more Smart Citations